Migration, Human Capital Formation, and Long-Run Output - Oded Galor; Oded Stark (Migration: A challenge for Europe. Symposium 1993, 1994)
Interest in the effects of labor migration on the receiving economy has not produced ample insights regarding its long-run consequences. Important as it may be, the impact on wages and employment, especially on groups whose labor market characteristics are similar to those of migrants, could be transitory. With very few exceptions (e.g., Galor, 1986), the existing migration literature has not provided a coherent analysis confirming that any such effect could not be reversed in the long run. Conversely, the analysis of the transition and steady-state repercussions of migration that arise even if migration has no effect at all on standard labor market variables such as wages and employment is yet to be pursued. This paper takes a step in this direction. We focus on one particular characteristic of migrants, viz., the level of human capital, and explore its repercussions. (...)
Keywords: F22; J24; 330; migration; human capital